2010
DOI: 10.1093/ndtplus/sfq032
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different synthetic membranes on laboratory parameters and survival in chronic haemodialysis patients

Abstract: Background. A number of studies suggested that the type of dialysis membrane is associated with differences in long-term outcome of patients undergoing haemodialysis, both in terms of morbidity and mortality. In the majority of dialysis units, synthetic membranes are being used. However, no studies are available so far for comparison between different biocompatible membranes. Therefore, we studied the influence of high- and low-flux polysulphone membranes (PS) in comparison with polymethylmethacrylate (PMMA) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 78 publications
(41 reference statements)
0
17
0
Order By: Relevance
“…Kreusser et al [38] reported that the cumulative 5-year survival rate for dialysis patients treated with PMMA membrane is higher than that of patients treated with PS membrane (68 vs. 54%). PES membranes are a variant of PS, designed for better clearance of high-molecular weight toxins while restricting the albumin passage.…”
Section: Discussionmentioning
confidence: 99%
“…Kreusser et al [38] reported that the cumulative 5-year survival rate for dialysis patients treated with PMMA membrane is higher than that of patients treated with PS membrane (68 vs. 54%). PES membranes are a variant of PS, designed for better clearance of high-molecular weight toxins while restricting the albumin passage.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 The results of previous studies that evaluated the possible clinical advantages of HDF in comparison with HD are not consistent, and it is not possible to make any precise conclusion out of them. [17][18][19][20][21] Compared with low-flux dialysis, high-flux HD might have a beneficial effect on mortality and clinical outcomes in the patients [22][23][24][25][26][27] or not. 28 The use of synthetic high-flux membranes should be considered to delay the longterm complication of HD therapy: amyloidosis, hyperphosphatemia, cardiovascular risk, and anemia.…”
Section: Introductionmentioning
confidence: 99%
“…9). Previous articles have reported the improvements of various clinical symptoms with the conventional PMMA dialyzers [3][4][5][9][10][11][12][13][14][15][16][17][18][19]. Protein adsorption by PMMA membranes is considered one factor associated with these improvements.…”
Section: Discussionmentioning
confidence: 99%